Hand hygiene knowledge,attitude and practices among health care workers of Pietersburg Tertiary Hospital, Polokwane, Limpopo Province - Setati, Musa Eileen (My University, 2019)
Background: Health care workers (HCWs) hands are the most common vehicle for the transmission of health care associated infections (HCAIs) between patients and the health care environment. Hand hygiene is regarded as the most important, simplest, and least expensive means of reducing the burden of HCAIs. However, hand hygiene compliance remains low among HCWs. Aim: To assess the level of knowledge, attitude and self-reported practices (KAP) of HCWs on hand hygiene and associated factors. Method: A quantitative, descriptive study using a pre-tested self-administered questionnaire was conducted among HCWs of Pietersburg Hospital. Data collection was carried out between January and February 2018. KAP scores were summarised into means, standard deviations and percentages. Chi-square and Fisher’s exact tests were used to determine association between KAP scores and selected independent variables (gender, age, profession, experience, discipline and training). Results: There were 324 respondents, mostly females (74.3%), <40 years (70.6%) and predominantly nurses (52.4%). Majority had moderate knowledge (79.3%), positive attitude (88.8%) and good practices (87.9%). Respondents had knowledge gaps on HCAIs, WHO “Five (5) moments for hand hygiene” and alcohol based hand rub. Association was found between respondent’s KAP scores and age (p<0.05). Nursing profession was associated with good practices (p=0.000). Knowledge and attitude were associated with years of clinical experience (p<0.05). Positive attitude (p=0.019) and good practices (p=0.000) were associated with training in the last 3 years. No significant relationship was found between KAP and undergraduate training. Conclusion: Most respondents had moderate knowledge, positive attitude and good practices. Respondent’s variety in KAP scores and associated factors indicate that a multimodal, multifaceted improvement approach should be undertaken to address KAP gaps.
Thesis(M. Med. (Public Health Medicine)) -- University of Limpopo, 2019
Keywords: Hand hygiene; Knowledge; Attitude; Practices; HCAIs; Hygiene; Medical care; Hand -- Care and hygiene; Hand washing